The Positron Passport: An Essay-Poem in Quantum Poetics. Issue 3 (September 2021) - Catanzano, Amy
Abstract : This essay-poem develops the author's ongoing transdisciplinary examination of her integrated artistic practice and theory known as 'quantum poetics', investigating shared principles in poetry and science with the aim of reinventing common notions of spacetime, language, and reality. Topics touched upon include her research in particle physics at the European Organization for Nuclear Research (CERN) and Canfranc Underground Laboratory, the uncertainty principle in quantum theory and aesthetic ambiguity, Werner Heisenberg's essays on language and science, the reader of a literary text in relation to an observation in quantum theory, string theory and poetry, the asymmetry of matter and antimatter in the known universe in relation to the imagination, and the poethics of science. Using a cross-genre form that includes poetry, creative nonfiction, and academic scholarship identified as an essay-poem, the author writes in 'windows', justified text blocks that transition into and out of original poetry and quoted material by writers and scientists. One purpose of these windows is to treat the spacetime of the page as a literary device, one that visually foregrounds the material construct of literary language.